2007
DOI: 10.1248/cpb.55.957
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Sulfuric Acid Catalyzed One-Pot Three-Component Synthesis of Imidazoazines

Abstract: Imidazoazines have been synthesized by a one-pot three-component condensation reaction of an aldehyde, a 2-aminoazine and an isocyanide in the presence of the cellulose sulfuric acid, as an effective bio-supported catalyst in excellent yields. The reaction work-up is simple and the catalyst can be easily separated from the product and reused in several times.Key words cellulose sulfuric acid; bio-supported catalyst; imidazo[1,2-a]pyridine; isocyanide; multi-component reaction Imidazo[1,2-a]pyridines, as an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(15 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…To the best of our knowledge, the synthesis of compounds 6f, 7b, 7c, 7e-7f are new and have not been reported in the literature so far. Apart from the above mentioned reagents, in general imidazo [1,2-a]pyridines have been reported to be synthesized by different methodologies for this type of condensation reactions such as Sc(OTf)3 [38], ZnCl2 [39], MgCl2 [40], ZrCl4 [41], SnCl2·2H2O [42], HClO4 [27], AcOH [28], p-TSA [43], montmorillonite K-10 [44], cellulose sulfuric acid [26], catalyst free and solvent free reaction condi-tions [45,46]. Most of these methods have many limitations in terms of lower product yields, toxicity, longer reaction time, higher energetic reaction conditions or use of hazardous and volatile organic solvents like acetonitrile, toluene, chloroform etc.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, the synthesis of compounds 6f, 7b, 7c, 7e-7f are new and have not been reported in the literature so far. Apart from the above mentioned reagents, in general imidazo [1,2-a]pyridines have been reported to be synthesized by different methodologies for this type of condensation reactions such as Sc(OTf)3 [38], ZnCl2 [39], MgCl2 [40], ZrCl4 [41], SnCl2·2H2O [42], HClO4 [27], AcOH [28], p-TSA [43], montmorillonite K-10 [44], cellulose sulfuric acid [26], catalyst free and solvent free reaction condi-tions [45,46]. Most of these methods have many limitations in terms of lower product yields, toxicity, longer reaction time, higher energetic reaction conditions or use of hazardous and volatile organic solvents like acetonitrile, toluene, chloroform etc.…”
Section: Resultsmentioning
confidence: 99%
“…As it can be seen, these heteropolyacids are more effective than other catalysts, 7 being compared economically and environmentally attractive and effective catalysts for various reactions and having high capability in practical uses. 23 The efficiency of various heteropolyacids has also been compared ( …”
Section: Methodsmentioning
confidence: 99%
“…6 As a result, numerous two-and three-component approaches for their synthesis have been reported. [7][8][9][10][11][12][13][14] The amino group at position 2 confers special properties to this nucleus, which has been used to prepare 2-aminoimidazo[1,2-a]pyridines as anti-rhinovirus agents. 15 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, EMF could be also synthesized in good yield (72.5%) directly from the fructose through one-pot reaction, which included that the dehydration of fructose into HMF, followed by etherification of HMF into EMF. Shaabani and co-workers 44 have also developed a high yielding synthesis of imidazoazine derivatives through the one-pot three-component condensation reaction of aldehydes, 2-aminoazine and isocyanides in the presence of catalytic amount of cellulose sulfuric acid (CSA), as an effective bio-supported catalyst in methanol at room temperature (Scheme 15). The results showed that the efficiency and the yield of the product in methanol were higher than those obtained in other solvents like water, ethanol, dichloromethane, toluene, acetonitrile and solventfree condition.…”
Section: Scheme 4 Diazotization and Iodination Catalyzed By Csamentioning
confidence: 99%